2011
DOI: 10.1128/aac.01022-10
|View full text |Cite
|
Sign up to set email alerts
|

The Marine Sponge-Derived Polyketide Endoperoxide Plakortide F Acid Mediates Its Antifungal Activity by Interfering with Calcium Homeostasis

Abstract: Plakortide F acid (PFA), a marine-derived polyketide endoperoxide, exhibits strong inhibitory activity against the opportunistic fungal pathogens Candida albicans, Cryptococcus neoformans, and Aspergillus fumigatus. In the present study, transcriptional profiling coupled with mutant and biochemical analyses were conducted using the model organism Saccharomyces cerevisiae to investigate the mechanism of action of this compound. PFA elicited a transcriptome response indicative of a Ca 2؉ imbalance, affecting the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 36 publications
3
41
0
Order By: Relevance
“…Another marine-derived polyketide, endoperoxide plakortide F acid (PFA), was found to elicit a transcriptomic response indicative of a Ca 2ϩ imbalance. This response affected the expression of genes known to be responsive to altered cellular calcium levels and strongly inhibited the opportunistic fungal pathogens Candida albicans, Cryptococcus neoformans, and Aspergillus fumigatus (107). The authors showed that calcium transporters, including those with pmr1/pmr1 and pmc1/pmc1 mutations, were sensitive to PFA, and this finding agreed with the transcriptional response to PFA, which appears to be indicative of Ca 2ϩ overload-related stress.…”
Section: Interference With the Calcium Secretory System On The Endomesupporting
confidence: 77%
“…Another marine-derived polyketide, endoperoxide plakortide F acid (PFA), was found to elicit a transcriptomic response indicative of a Ca 2ϩ imbalance. This response affected the expression of genes known to be responsive to altered cellular calcium levels and strongly inhibited the opportunistic fungal pathogens Candida albicans, Cryptococcus neoformans, and Aspergillus fumigatus (107). The authors showed that calcium transporters, including those with pmr1/pmr1 and pmc1/pmc1 mutations, were sensitive to PFA, and this finding agreed with the transcriptional response to PFA, which appears to be indicative of Ca 2ϩ overload-related stress.…”
Section: Interference With the Calcium Secretory System On The Endomesupporting
confidence: 77%
“…Similarly, the mechanism of antifungal action involves permeabilization of the fungal membrane (Sionov et al 2005; Wong et al 2012). However, the mechanism has been studied in only a few cases (Shi et al 2012; Sionov et al 2005; Xu et al 2011b). A variety of viruses including herpes simplex virus, fish nodavirus, fish nodavirus, influenza virus A and B, respiratory syndrome virus, porcine reproductive virus, tobacco mosaic virus, human metapneumovirus, human immunodeficiency virus, hepatitis C virus, herpes simplex virus, human cytomegalovirus, and white spot syndrome virus are produced by bacteria, fungi, algae, cnidarians, crustaceans, echinoderms, tunicates, and fish.…”
Section: Discussionmentioning
confidence: 99%
“…Plakortide F acid induced transcription of a lacZ reporter gene activated by the calcineurin-dependent response element. A rise in intracellular calcium levels occurred in response to plakortide F acid (Xu et al 2011b). …”
Section: Antifungal Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…These sets were chosen since they are well studies and the relative simplicity in having a control set and an experimental set; they were downloaded from the Gene Expression Omnibus on September 12, 2014. The series are: GSE 10073, which measures yeast gene expression in the presence of sampangine, and alkaloid [17]; GSE 26925, which measures the effects of plafortide F acid [18]; and GSE 7820, which measures two different strains of yeast under rich and nitrogendeficient conditions [19].…”
Section: Methodsmentioning
confidence: 99%